Wicked for you ebook - Black, Shayla (Wicked Lovers, 2015)
Another "searingly sexy"* romance awaits in the latest Wicked Lovers novel from the  New York Times  bestselling author of  His to Take.   Ever since he rescued her from a dangerous kidnapper, Mystery Mullins has wanted Axel Dillon. When he returned her to her Hollywood father and tabloid life, she was grateful…and a little in love. Mystery wasn’t ready to let Axel go, even after the soldier gently turned her away because, at nineteen, she was too young.   Now, six years later, Mystery is grown, with a flourishing career and a full life—but she’s still stuck on Axel. Disguised, she propositions him in a bar, and the night they spend together is beyond her wildest dreams. Mystery steels herself to walk away—except the sheets are barely cold when her past comes back to haunt her.   Once he realizes Mystery isn’t the stranger he thought, Axel is incensed and intrigued. But when it’s clear she’s in danger, he doesn’t hesitate to become her protector—and her lover—again. And as the two uncover a secret someone is willing to kill for, Axel is determined to claim Mystery’s heart before a murderer silences her for good. *Maya Banks, #1  New York Times  bestselling author